A Paradox in Digital Memory Assessment: Increased Sensitivity With Reduced Difficulty - White, Joshua P.; Schembri, Adrian; Edgar, Chris J.; Lim, Yen Ying; Masters, Colin L.; Maruff, Paul (Frontiers in Digital Health, 2021)
The One Card Learning Test (OCL80) from the Cogstate Brief Battery—a digital cognitive test used both in-person and remotely in clinical trials and in healthcare contexts to inform health decisions—has shown high sensitivity to changes in memory in early Alzheimer's disease (AD). However, recent studies suggest that OCL sensitivity to memory impairment in symptomatic AD is not as strong as that for other standardized assessments of memory. This study aimed to improve the sensitivity of the OCL80 to AD-related memory impairment by reducing the test difficultly (i.e., OCL48). Experiment 1 showed performance in healthy adults improved on the OCL48 while the pattern separation operations that constrain performance on the OCL80 were retained. Experiment 2 showed repeated administration of the OCL48 at short retest intervals did not induce ceiling or practice effects. Experiment 3 showed that the sensitivity of the OCL48 to AD-related memory impairment (Glass's Δ = 3.11) was much greater than the sensitivity of the OCL80 (Glass's Δ = 1.94). Experiment 4 used data from a large group of cognitively normal older adults to calibrate performance scores between the OCL80 and OCL48 using equipercentile equating. Together these results showed the OCL48 to be a valid and reliable test of learning with greater sensitivity to memory impairment in AD than the OCL80.